(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione negli Atti del Seminario Internacional de Profesores sul tema“Neutralidad del estado, religiones e ideologías”, organizzato dall’Universidad Complutense, tenutosi a Madrid il 21 novembre 2013. SOMMARIO: 1. Le nuove “guerre di religione”: tra credenti e noncredenti – 2. Lo spazio pubblico urbano: a) la posizione di simboli religiosi – 3. (segue:) b) la rimozione di simboli preesistenti – 4. Lo spazio pubblico istituzionale: rimozione e posizione di simboli religiosi - 5. Dal processo conflittuale a quello mediatorio – 6. Riflessi del processo di mediazione sui simboli religiosi. ABSTRACT Religious Symbols and Alternative Proceedings Religious symbols are becoming the object of a new forum of the ancient religious wars: those between believers and nonbelievers instead of between different organized religions like in the past. The Author describes the numerous judgements that were passed in the last years by U.S. and European Courts with particular reference to two kinds of public space: roads, parks, ecc. and public buildings. But he points out that the the ordinary trial is ineffective for resolution of cultural and religious conflicts and holds the utility of an alternative proceeding: the mediation between believers and nonbelievers, always in respect of liberty of conscience for everyone.